Interactions between coherent twin boundaries and phase transition of iron under dynamic loading and unloading - Wang, Kun; Chen, Jun; Zhang, Xueyang; Zhu, Wenjun (Journal of applied physics, 2017)
Phase transitions and deformation twins are constantly reported in many BCC metals under high pressure, whose interactions are of fundamental importance to understand the strengthening mechanism of these metals under extreme conditions. However, the interactions between twins and phase transition in BCC metals remain largely unexplored. In this work, interactions between coherent twin boundaries and α ↔ ε phase transition of iron are investigated using both non-equilibrium molecular dynamics simulations and the nudged elastic band method. Mechanisms of both twin-assisted phase transition and reverse phase transition are studied, and orientation relationships between BCC and HCP phases are found to be 11 1 ¯ B C C | | 1 ¯ 2 1 ¯ 0 H C P and 1 1 ¯ 0 B C C | | 0001 H C P for both cases. The twin boundary corresponds to 10 1 ¯ 0 H C P after the phase transition. It is amazing that the reverse transition seems to be able to “memorize” and recover the initial BCC twins. The memory would be partly lost when plastic slips take place in the HCP phase before the reverse transition. In the recovered initial BCC twins, three major twin spacings are observed, which are well explained in terms of energy barriers of transition from the HCP phase to the BCC twin. Besides, the variant selection rule of the twin assisted phase transition is also discussed. The results of present work could be expected to give some clues for producing ultra-fine grain structures in materials exhibiting martensitic phase transition.